1987
DOI: 10.1063/1.452987
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast conformation equilibration in triphenyl methane dyes analyzed by time resolved induced photoabsorption

Abstract: Dual frequency pump–probe induced photoabsorption recovery is studied in two triphenylmethane dyes, malachite green and crystal violet, using femtosecond laser pulses. Comparison of the decays observed for different polarization conditions allows us to analyze the symmetry of electronic states. We observe that the simplest C2 or D3 symmetries cannot account for all our observations. In addition to the previously reported electronic relaxation decays, we observe two additional subpicosecond relaxation component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 27 publications
7
53
0
Order By: Relevance
“…The isomerization dynamics were best characterized by a single exponential decay (2.0 + 0.3 ps at the air/aqueous interface). These rates are significantly slower than the dominant decay component of ~ 0.7 ps reported for malachite green in bulk water [49][50][51].…”
Section: Resultsmentioning
confidence: 71%
“…The isomerization dynamics were best characterized by a single exponential decay (2.0 + 0.3 ps at the air/aqueous interface). These rates are significantly slower than the dominant decay component of ~ 0.7 ps reported for malachite green in bulk water [49][50][51].…”
Section: Resultsmentioning
confidence: 71%
“…The decay times obtained with MG agree very well with earlier findings. 24,31,33 The data reported for BG are scarce and refer only to single-color pump-probe experiments carried out at 635 nm 33 with a temporal resolution of approximately 30 fs. The authors have found two time constants shorter than 250 fs as well as three longer values: 0.55, 0.69, and 2.7 ps.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason MG has been the subject of numerous stationary and time-resolved spectroscopic experiments that aimed to describe its deactivation pathway. [28][29][30][31][32][33][34][35] It is generally agreed that the relaxation is intrinsically barrierless and involves rotation of the aniline or phenyl substituents. The friction exerted by the environment on the rotating rings accounts for the viscosity dependence of the excited state lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, this process is slightly solvent dependent and involves torsional re-equilibration of the excited state. 33,35 The shortest time constant found here, τ b1 , can be associated with this relaxation step. This process is followed by a nonradiative transition to an intermediate state S x .…”
mentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Excitation of MG in the S 0 -S 1 transition is followed by ultrafast relaxation from the Franck-Condon S 1 state to equilibrium. According to the literature, this process is slightly solvent dependent and involves torsional re-equilibration of the excited state.…”
mentioning
confidence: 99%